Form of Services on Community-Based Employment Skills Education for People with Disabilities in Rural Areas - Syamsi, Ibnu (Journal of Education for Sustainability and Diversity, 2022)
Form of services on community-based employment skills education for people with disabilities in rural areas. This study aims to describe the form of community-based vocational education mobile services for people with disabilities in rural areas. This type of qualitative descriptive research using data collection tools, observations, interviews, and documentation. The results of the study, which obtained basic data on village potential, especially those related to the problems of people with disabilities in the research area, obtained basic data on prevalence rates of people with disabilities in rural areas, classification of disabilities, need assessments, and their distribution who need to receive job skills education services through mobile services, successful preparation of training materials to prepare prospective tutors to implement skills training, successful training of a number of prospective tutors in the village to train job skills, successful initiating efforts to raise funds and development in the research village area, successful instilling an understanding and awareness among community members, especially people parents or families with disabilities, regarding the importance of paying attention to or solving the problems of people with disabilities in rural areas.